2015
DOI: 10.1124/mol.114.097345
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Dual Inhibitor of SRPK1 and CK2 That Attenuates Pathological Angiogenesis of Macular Degeneration in Mice

Abstract: Excessive angiogenesis contributes to numerous diseases, including cancer and blinding retinopathy. Antibodies against vascular endothelial growth factor (VEGF) have been approved and are widely used in clinical treatment. Our previous studies using SRPIN340, a small molecule inhibitor of SRPK1 (serinearginine protein kinase 1), demonstrated that SRPK1 is a potential target for the development of antiangiogenic drugs. In this study, we solved the structure of SRPK1 bound to SRPIN340 by X-ray crystallography. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 64 publications
6
42
0
4
Order By: Relevance
“…However, the results of the different cell types in our analysis were comprehensible, with CNV-derived RPE showing more similarities to hRPE and fewer with ARPE-19. Expression data of ARPE-19 was comparable to that of published datasets [35].…”
Section: Discussionsupporting
confidence: 66%
“…However, the results of the different cell types in our analysis were comprehensible, with CNV-derived RPE showing more similarities to hRPE and fewer with ARPE-19. Expression data of ARPE-19 was comparable to that of published datasets [35].…”
Section: Discussionsupporting
confidence: 66%
“…Three chemical scaffolds have been described with inhibitory activities against SRPK1 (Batson et al, 2017; Morooka et al, 2015; Fukuhara et al, 2006; Siqueira et al, 2015; Székelyhidi et al, 2005; Gammons et al, 2013), and, among them, SPHINX31 was recently derived from SPHINX and reported to have much improved potency (Batson et al, 2017). Although high-throughput screening has been commonly used to generate lead compounds in kinase inhibitor projects, we chose to query existing kinase inhibitor libraries and known FDA-approved drugs for their potential abilities to target SRPK1, an approach that offers advantages in expediting structure-activity relationship (SAR) studies and optimizing pharmacological properties.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our observations indicate that the manipulation of alternative splicing regulation may be a potential therapeutic target for HPV-related cancer. While a chemical inhibitor that targets splicing factors themselves has not been developed yet, the recent development of kinase inhibitors working upstream of splicing factors, such as CDC2-like kinase (CLK) (77)(78)(79) or SR protein kinase (SRPK) (80)(81)(82) for SR protein phosphorylation, may provide a way to block splicing factor activity. Alternatively, splicing cis elements may also be targeted, given the recent development of modified therapeutic oligonucleotides able to modulate splicing regulation (83)(84)(85)(86).…”
Section: Discussionmentioning
confidence: 99%